Applying the critical speed concept to racing strategy and interval training prescription - Pettitt, R. W. (International Journal of Sports Physiology and Performance, 2016)
The use of personal records (PRs) for running different distances may be used to derive critical speed (CS) and the finite capacity for running speeds exceeding CS (D'). Using CS and D', individualized speed-time and distance-time relationships can be modeled (ie, time limits associated with running at a given speed or a given distance can be derived via linear regression with a high degree of accuracy). The running 3-min all-out exercise test (3 MT) has emerged as a method for estimating CS and D' on a large group of athletes in a single visit. Such a procedure is useful when PRs are not readily available (eg, team-sport athletes). This article reviews how to administer and interpret the running 3 MT, how CS and D' can inform racing strategy, and how CS and D' can be used to prescribe and evaluate high-intensity interval training (HIIT). Directions for deriving HIIT bouts using either fixed distances or fixed speeds are provided along with CS dose-responses to short-term HIIT programs.